Optimization of metronidazole tablet formulation using Manihot utilissima starch and a combination of processing techniques - Nnabuike D. Nnamani; Tochukwu J.N. Okonkwo (SpringerOpen, 2017)
The study aimed at optimizing the formulation of metronidazole tablet with Manihot utilissima starch. Starch from one year old Manihot utilissima plant was extracted, processed and analyzed. The processed Manihot ultilissima starch and corn starch (reference standard) were used as formulation test polymers. A physical blend of metronidazole and starch polymer at 4:1, 2:1 and 1:1, was triturated with water/ethanol (1:1) solution of metronidazole, dried and blended with other formulation excipients and pulverized to size for compression. The FT - IR absorption spectrum of the metronidazole-Manihot ultilissima starch add mixture showed no chemical incompatibility. The metronidazole granules containing Manihot ultilissima starch had better particle size distribution and other micromeritic qualities in comparison with formulations of corn starch. Metronidazole tablets produced with the Manihot ultilissima starch gave good compact (9-10 Kgf hardness) and low friability. Using a 6 × 3 contingency table for Two-way analysis of variance (ANOVA) in design without repeated values, and the effect of the starch polymer concentrations on metronidazole dissolution was analyzed. The F-ratio results were greater than the critical value of F-table; and therefore the null hypothesis that the effects of all treatment at different concentration are the same at 5% P value was rejected. The variation from critical difference was more significant at ratio 1:1 of corn and Manihot ultilissima starches. In conclusion, the 1:1 ratio of metronidazole and Manihot ultilissima starch using a combination of co-solvency, particle size reduction and solid dispersion techniques gave optimal tablet formulation.